Veterinary Drug Development from Indonesian Herbal Origin: Challenges and Opportunities - Yedi Herdiana; Nasrul Wathoni; Sriwidodo Sriwidodo; I Ketut Madite Adnyane (Universitas Padjadjaran (Unpad), 2021)
Herbal medicine is increasingly being used in human and veterinary medicine to reduce and prevent minor ailments and support conventional treatment using allopathic medicine. The medicinal properties of the plants used in phytotherapy are due to the large number of active compounds found in the plant kingdom. The active compounds extracted from the plant is often equivalent to a synthetic drug according to its therapeutic efficacy; thus, they are used in veterinary medicine, primarily as antibacterial, antimycotic, antiparasitic, disinfect, and immunostimulant.pharmaceutical quality, ensuring safety, specific standards of purity, and consistency. These standards apply throughout the production and formulation process. This review describes the development of herbs that can be used as veterinary drugs with the possibility of dosage form technology. Veterinary dosage forms show great promise for the future of the herbal veterinary delivery system.Keywords: Veterinary drug, herbal medicine, dosage form, drug delivery.